Patient Perspectives about Mild Cognitive Impairment: A Systematic Review. Issue 3 (27th May 2022) - Blatchford, Lisa; Cook, Julia
ABSTRACT: Objectives: Mild cognitive impairment (MCI) is a concept that is steeped in controversy not limited to prognostic uncertainty; it is unclear how patients interpret or attribute meaning to the label, and whether they perceive that being made aware is beneficial. Methods: A systematic review was conducted, searching ISI Web of Science, PubMed and PsycINFO in accordance with PRISMA guidelines. Search terms were developed to include articles concerning perceptions regarding MCI and experiences and impact of being informed. Thematic synthesis was applied to the findings. Results: Fourteen papers met criteria. Three themes emerged regarding the MCI label: 1) Individual differences relating to living circumstances, personal perceptions and experiences, and coping style affect how patients adjust to the MCI label; 2) Patients' reactions to the MCI label and their perceptions about how useful it was to receive are affected by the nebulous nature of the construct and information available regarding MCI; 3) Care partners are uncertain about what MCI means and how to address and cope with the patient's cognitive difficulties. Conclusions: Patient and care partner perspectives were affected by the quality of information and support provided, possibly influenced by clinicians' understanding of the concept. Personal perceptions and experiences, living circumstance and coping styles also shaped experiences of being informed. Clinical Implications: Clinicians should develop their understanding of MCI to deliver clear information to patients and consider the necessity of applying the label. Offering support tailored to patients' specific needs may improve perceptions about the label's utility, whilst aiding coping and adjustment.